Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Shuyan Wang; Ying Xiong; Hushun Zhang; Dade Song; Yanping Wang; Hui Ge; Chengbin Zhang; Long Liang; Xiaming Zhong (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus . Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year -1 , and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year -1 , 0.79 year -1 , and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.

Assessment of ecological damage from illegal fishing and judicial practice for damage compensation - Hushun Zhang; Dongjia Li; Xiaming Zhong; Ying Xiong (Ocean & Coastal Management, 2023)

Dynamic valuation of the provisioning services of marine fisheries ecosystem based on BeiDou VMS data: A case study of TACs project for Acetes chinensis in the Yellow Sea - Guodong Li; Dongjia Li; Ying Xiong; Xiaming Zhong; Jinjin Shi; Hushun Zhang; Dade Song; Fan Yang; Zhongjie Kang; Xiaorui Wu; Shuyan Wang; Long Liang (Ocean & Coastal Management, 2023)

Single-cell RNA sequencing to reveal non-parenchymal cell heterogeneity and immune network of acetaminophen-induced liver injury in mice - Xiaoyun Li; Yang Zhi; Jing Li; Xiaohong Lei; Yi Ju; Yuting Zhang; Yufan Zheng; Xiaming Kong; Feng Xue; Wei Zhong; Xiaoyu Chen; Jieting Tang; et al. (Archives of Toxicology, 2023)

Changes in overwintering ground of small yellow croaker ( Larimichthys polyactis ) based on MaxEnt and GARP models: A case study of the southern Yellow Sea stock - Guodong Li; Ying Xiong; Xiaming Zhong; Dade Song; Zhongjie Kang; Dongjia Li; Jianhua Tang; Yanping Wang; Lei Wu (Journal of Fish Biology, 2023)
Small yellow croaker ( Larimichthys polyactis ), a commercially essential fish commonly caught in China and South Korea, is now facing a severe decline in resources. The recruitment and surplus of L. polyactis depend selecting a suitable marine environment for overwintering. However, the international overwintering migration habit of L. polyactis limits the investigation of its overwintering environment preferences and suitable grounds. In this study, based on the distribution data of L. polyactis in the southern Yellow Sea in winter from 2010 to 2019 and ocean remote sensing data such as sea bottom temperature (SBT), sea bottom salinity, chlorophyll‐a concentration and water depth (Depth), we used the maximum entropy (MaxEnt) and the genetic algorithm for rule‐set production (GARP) models to investigate the overwintering grounds of the southern Yellow Sea stock (SYS). The jackknife test was used to assess the importance of various environmental factors. For modelling the overwintering ground distribution of SYS, the area under the curve values of both models ​were higher than 0.9. The overwintering ground was at 32°10′ N–33°48′ N, 122°30′ E–125°00′ E. The direction of its distribution was consistent with the Yellow Sea Warm Current in the southern Yellow Sea during the winter. Compared with the suitable overwintering area during 2010–2014, the highly appropriate overwintering area for SYS to overwinter decreased significantly during 2015–2019, showing a trend of moving to the east and north, related to the increase in fishing pressure and strengthening of the Yellow Sea Warm Current in recent years. Depth was the most significant factor for SYS overwintering, followed by SBT. The overwintering ground was at a depth of 40–65 m during the two periods. Additionally, the suitability of overwintering grounds in the coastal waters of south‐western South Korea has gradually increased. This study provides a scientific basis for formulating effective strategies to manage L. polyactis resources under the China–South Korea Fisheries Agreement.

Isotopic Evidence of Population Connectivity at Multiple Life Stages for Larimichthys polyactis in the Southern Yellow Sea and East China Sea - Dade Song; Ying Xiong; Tao Jiang; Jian Yang; Zhongjie Kang; Xiaming Zhong; Dongyan Liu (Fishes, 2023)
Larimichthys polyactis, a typically oceanodromous species found across the East China, Yellow, and Bohai Seas, is one of the most ecologically and commercially important species in East Asian countries. Moreover, over the past decades, L. polyactis has experienced significant changes in its biological characteristics under long-term intensive fishing pressure, suggesting a need for urgent protection. A robust understanding of connectivity at the spatiotemporal scale is critical for the effective and thorough management of L. polyactis. In the present study, the otolith stable carbon (δ13C) and oxygen (δ18O) isotope ratios of four adult L. polyactis groups (Y-1–4) sampled in the southern Yellow and East China Seas (SYS and ECS) were determined at multiple life stages, including the larval dispersal period (core), overwintering period (A1), and one whole life cycle except the post-spawning period (A2). Dunn’s multiple comparison test showed that there was no difference among the Y-1, Y-2, and Y-3 groups in the otolith core and A1 zones (p > 0.05); the otolith δ13C and δ18O of the Y-4 group were significantly higher than those of the Y-3 group (p

Early life migration and population discrimination of the small yellow croaker Larimichthys polyactis from the Yellow Sea: inferences from otolith Sr/Ca ratios - Dade Song; Ying Xiong; Tao Jiang; Jian Yang; Xiaming Zhong; Jianhua Tang (Journal of Oceanology and Limnology, 2022)

Evaluation of Spawning- and Natal-Site Fidelity of Larimichthys polyactis in the Southern Yellow Sea Using Otolith Microchemistry - Dade Song; Ying Xiong; Tao Jiang; Jian Yang; Xiaming Zhong; Jianhua Tang; Zhongjie Kang (Frontiers in Marine Science, 2022)
Small yellow croaker Larimichthys polyactis is an important commercial fish species; however, industrial-scale fishing has largely contributed to the changes in its biological characteristics, such as individual miniaturization, faster growth, and younger average age. Robust understanding of the pivotal life history of L. polyactis , a typical oceanodromous species, is needed for its conservation and restoration. However, L. polyactis fidelity to natal or spawning sites is not well understood and, at present, there is no effective management strategy to guarantee the sustainable exploitation of L. polyactis . This study used laser ablation inductively coupled plasma-mass spectrometry to analyse the elemental composition of otoliths from 60 adult yellow croakers caught in the southern Yellow Sea, including two spawning groups with 1- and 2-year-old fish (S1 and S2, respectively) sampled close to China and one overwintering group including two-year-old fish (O2) sampled close to South Korea. The ratios of elements (Li, Na, Sr, and Ba) to Ca in the otolith core zones were significantly higher ( P < 0.05) than in those of the year one (Y1) and year two (Y2) annual rings, but there were no significant differences in the elemental ratios between the Y1 and Y2 zones. Principal component analysis (PCA) of the elemental otolith signatures of the core, Y1, and Y2 zones in the three groups revealed two distinct clusters (cluster 1: S1-core, S2-core, and O2-core zones; cluster 2: S2–Y1, O2–Y1, S2–Y2, and O2–Y2 zones) and one zone (S1–Y1), suggesting spawning-site fidelity and natal-site fidelity uncertainty, especially considering the dispersal by current in prolonged period (50 h) from fertilized eggs to hatching and internal effect, such as yolk sac and maternal effect. Furthermore, these results indicated that the S2 and O2 groups could represent the same population, suggesting a stable migratory route for L. polyactis in Chinese and South Korean waters, whereas the S1 group could represent another population. This suggests the possibility a mixed L. polyactis population in the southern Yellow Sea. Characterization L. polyactis spawning-site fidelity is a crucial step toward linking spawning-site fidelity of this overexploited species with thorough conservation and management strategies.

Early life history of the small yellow croaker ( Larimichthys polyactis ) in sandy ridges of the South Yellow Sea - Ying Xiong; Jian Yang; Tao Jiang; Hongbo Liu; Xiaming Zhong; Jianhua Tang (Marine Biology Research, 2017)

Migration and population structure characteristics of the small yellow croaker Larimichthys polyactis in the southern Yellow Sea - Ying Xiong; Xiaming Zhong; Jianhua Tang; Jian Yang (Acta Oceanologica Sinica, 2016)